Phūmpanyā Thai nai ngān sin thin M̄ưang Krung = Bangkok regional wisdom through art and craft - Kamth̨̄onthēp Kratāith̨̄ong (Samnak Bōrānnakhadī læ Phiphitthaphanthasathān h̄æng Chāt, Krom Sinlapāk̨̄on, Krasūang Sưksāthikān, 2000)
On handicrafts and small art works of Bangkok, Thailand; published to mark the inauguration festival of Thai heritage year, 7th June 2000.